Evaluation of Indoor and Outdoor Aquaculture Systems as Alternatives to Harvesting Hemolymph From Random Wild Capture of Horseshoe Crabs - Tinker-Kulberg, Rachel; Dellinger, Anthony L.; Gentit, Lisa C.; Fluech, Bryan A.; Wilder, Cole A.; Spratling, Ivy L.; Stasek, David J.; Kepley, Christopher L.; Robertson, Lee; Goddard, Melinda K.; Brady, Terry E.; Tōland, Lance; et al. (Frontiers in Marine Science, 2020)
This study evaluated two approaches to the aquaculture of Limulus polyphemus with the ultimate goal of harvesting Limulus amebocyte lysate (LAL) at an industrial scale. To monitor Horseshoe crabs (HSCs), a combination of physical, biochemical and cellular components were examined for HSC cohorts in an indoor recirculating aquaculture system (RAS) and an outdoor on-bottom pen culture system (PCS) over a 6-month period. The metrics included body weight, hemocyanin (Hc) concentration, amebocyte density, and LAL reactivity. In addition, a simulated biomedical bleeding event (extracting 30% of the total hemolymph volume) was performed to assess the impact on physiochemical properties of the hemolymph and amebocytes. Overall, the HSCs fared better in the RAS compared to the PCS, with higher rebound kinetics with respect to Hc, amebocyte density, LAL reactivity, and with 100% survival in the RAS cohort. Further, hemolymph reinfusion (after amebocyte removal) was shown to improve HSC recovery time. In summary, outcomes of this research show that a RAS, coupled with adequate nutrition and monitoring can provide HSCs with a suitable environment for sustainable hemolymph extraction and year-round LAL production.